Dorsal Fin Spines and Rays for Nonlethal Ageing of Goliath Grouper Epinephelus itajara - Jessica L. Carroll; Robert D. Ellis; Angela B. Collins; Debra J. Murie (Fishes, 2023)
Atlantic Goliath Grouper, Epinephelus itajara , the largest grouper in the western North Atlantic, exhibits life history characteristics (e.g., it is slow-growing, long-lived, and late-maturing) that make it particularly susceptible to fishing pressure. Otoliths, the structure typically processed for age determination, are usually collected as part of fishery monitoring, but otoliths are not available from Goliath Grouper due to a harvest moratorium enacted in 1990 for United States waters. Alternative structures—such as dorsal fin rays or spines—can be acquired for ageing via nonlethal sampling and may provide reliable age estimates. Since 2006, the Florida Fish and Wildlife Conservation Commission (FWC) has been collecting incidental Goliath Grouper samples from mortality events including those from cold kills and red tides. Corresponding otolith, dorsal fin ray and dorsal fin spine samples were compared to determine the accuracy and precision of the external ageing structures. Marginal increment analyses indicated that annulus (translucent zone) deposition occurred primarily in March–June on spines and in April–June on rays. While ages determined from both rays and spines exhibited high precision, the accuracy compared to otolith ages was low as a result of systematic underageing of both external structures, particularly at the oldest age classes. A correction factor was applied to rays and spines that remedied the underageing, but the correction factor was more successful for spines. An analysis of ray and spine section accuracy based on nonlethal structure removal from the fish (i.e., comparing ages from sections at the base of the structure within the body to those sectioned from the external surface of the body) determined that spines can be accurately aged when sampled distal of the base of the structure, but that rays cannot. Nonlethal sampling and ageing of Goliath Grouper spines facilitated by public participation could address management goals and help determine the offshore population age structure. ...